Non-linearities in real interest rate parity : evidence from OECD and Asian developing economies. - Baharumshah, Ahmad Zubaidi; Liew, Venus Khim Sen; Mittelhammer, Ron C. (Routledge, 2010)

(untitled)
This paper investigates the validity real interest rate parity (RIP) for a sample of 19 OECD and Asian developing economies. The distinction of this paper is that we exploit both linearity and non-linear unit root tests as advocated by Dufre´not et al. (Applied Economics, 38,pp. 203-229, 2006) to validate the parity. The major finding are: (i) the alignments from real interest rate differentials (RIDs) are corrected in a non-linear fashion and that the adjustments is asymmetric in both size and speed; (ii) that RIP holds for the developed and developing countries; and (iii) the empirical results are invariant with respect to the US, Japan or Germany as the centre country.